FINE STRUCTURE OF TRICHOBOTHRIA IN THE SALTICID SPIDER MARPISSA CALCUTTAENSIS - Abdul Khader Sultan Mohideen; Mohamed Habibullah (International Journal of Applied Biology, 2020)
The fine structure of trichobothria in the salticid spider Marpissa calcuttaensis (Tikader 1974) was investigated by scanning electron microscopy (SEM). The specimens were collected from the New College Campus, Chennai, India and kept in the laboratory before processing. The specimens were then fixed in Trump’s fixative followed by post fixation in 2% osmium tetraoxide at room temperature for 90 minutes. After that, the specimens were dehydrated in the graded ethanol series and hexamethyldisilazane dried. Lastly, the specimens were mounted on aluminum rods with araldite adhesive and coated with a thin layer of gold in a sputter coating unit and viewed under SEM. The SEM photomicrographs revealed the presence of trichobothria on the dorsal aspect of the first leg segments. The trichobothria were observed to be long and slender, embedded in special sockets. The articulation of the trichobothria in response to air deflections corresponds to that of other spider species. In addition, the slit-sensilla and lyriform organ were noticed on the tarsal area of the first leg may react to substrate vibrations which are in accordance to other arachnids. Thus, the structural characteristics features of the mechanoreceptors were compared with other arachnids to decipher their possible functional role and physiological significance.